Psychological masochism: A systematic review of the literature on conflicts, defenses, and motives. (4th May 2018) - Békés, Vera; Perry, J. Christopher; Robertson, Brian M.
Abstract: Objective: Our aim was to conduct a systematic review of the literature on psychological masochism to identify hypotheses for examination in clinical studies.Method: We identified defenses, conflicts, and motives using standardized measures in 23 psychoanalytic papers.Results: Three primary and three secondary subtypes of masochism emerged in the literature. Overall Gratification Inhibition (subtype I.1) was the "healthiest" form, associated with higher developmental level motives and neurotic defenses. The Global Conflict (I.2) was the least healthy form of masochism, consistent with personality disorder. It was associated with early developmental level motives and immature defenses, including depressive defenses, often associated with depression. Dominant Other (I.3) represented masochistic attachment problems, associated with early developmental level motives, object-related, image-distorting defenses, and narcissism. Of the secondary types, Separation–Abandonment (II.1) reflected object-related defenses, and separation-related motives. Rejection of Others (II.2) represented a sadistic-narcissistic form, associated with image-distorting and disavowal defenses, with both early and later developmental level motives. Finally, Sexual Pleasure vs. Guilt (II.3) was associated with autistic fantasy, and both early and later developmental level motives, suggesting a distinct traumatic origin and representing the juncture of sexual and psychological masochism.Conclusions: Analysts described six distinguishable types of masochism. Future studies should examine their validity.